PEMBENTUKAN KARAKTER (BANGSA) MELALUI OLAHRAGA - Syahruddin Syahruddin (STKIP Paris Barantai, 2014)
ABTRACTParticipation in athletics continue to become bodywork of our society. Individual participate in athletics for the education of, achievement, fitness, health, and recreation. But there also other reason like developing and characterÂ have socialization. Do athletics form character ? Role of important athletics becoming strategic and in context development of quality of SDM healthy, self-supporting, holding responsible, and measuring up to high kompetitif. Besides important also in development of identity, nationalism, and nation independence. Athletic which managed by professional will be able to lift nation prestige in international chess. History have noted that athletics can become education media or become business ikon and industry which is Â prospektif. Athletic potentially and aktual can become effective reference to forming of personality character and society characterÂ Keywords: Character and Sport